The Effects of Different Anesthesia Methods on the Treatment of Parkinson’s Disease by Bilateral Deep Brain Stimulation of the Subthalamic Nucleus - Lu, Yue; Chang, Lei; Li, Jinwen; Luo, Bei; Dong, Wenwen; Qiu, Chang; Zhang, Wenbin; Ruan, Yifeng (Frontiers in Neuroscience, 2022)
Background: Subthalamic nucleus deep brain stimulation (STN–DBS) surgery for Parkinson's disease (PD) is routinely performed at medical centers worldwide. However, it is debated whether general anesthesia (GA) or traditional local anesthetic (LA) is superior. Purpose: This study aimed to compare the effects of LA and GA operation method on clinical improvement in PD patients, including motor and non-motor symptoms, after STN–DBS surgery at our center. Method: A total of 157 PD patients were retrospectively identified as having undergone surgery under LA (n = 81) or GA (n = 76) states. Unified Parkinson's disease Rating Scale Motor Score (UPDRS-III) in three states, levodopa-equivalent-daily-dose (LEDD), surgical duration, intraoperative microelectrode recording (iMER) signal length, postoperative intracranial volume, electrode implantation error, neuropsychological function, quality of life scores and complication rates were collected and compared. All PD patients were routinely followed up at 6, 12, 18, and 24 months postoperatively. Result: Overall improvement in UPDRS-III was demonstrated at postoperative follow-up, and there was no significant difference between the two groups in medication-off, stimulation-off state and medication-off, stimulation-on state. However, UPDRS-III scores in medication-on, stimulation-on state under GA was significantly lower than that in LA group. During postoperative follow-up, LEDD in the LA group (6, 12, 18, and 24 months postoperatively) were significantly lower than the GA group; however, there were no significant differences at baseline or one-month between the two groups. The GA group had a shorter surgical duration, lower intracranial volume, and longer iMER signal length than the LA group. However, there was no significant group difference in electrode implantation accuracy and complication rates. Additionally, the Hamilton Anxiety Scale(HAMA) was significantly lower in the GA group than the LA group at one-month follow-up, but this difference disappeared at longer follow-up. And there was no significant group difference in PDQ-39 scale scores. Conclusion: Although both the groups showed overall motor function improvement without a significant postoperative difference, the GA group seemed superior in surgical duration, intracranial volume, and iMER signal length. As the accuracy of electrode implantation can be ensured by iMER monitoring, DBS with GA will become more widely accepted.